High-throughput analysis of thin-film stresses using arrays of micromachined cantilever beams - Kim, Hyun-Jong; Han, Jun-Hyun; Kaiser, Roy; Oh, Kyu Hwan; Vlassak, Joost J. (AMER INST PHYSICS, 2008)
We report on a technique for making high-throughput residual stress measurements on thin films by means of micromachined cantilever beams and an array of parallel laser beams. In this technique, the film of interest is deposited onto a silicon substrate with micromachined cantilever beams. The residual stress in the film causes the beams to bend. The curvature of the beams, which is proportional to the residual stress in the film, is measured by scanning an array of parallel laser beams generated with a diffraction grating along the length of the beams. The reflections of the laser beams are captured using a digital camera. A heating stage enables measurement of the residual stress as a function of temperature. As the curvature of each beam is determined by the local stress in the film, the film stress can be mapped across the substrate. This feature makes the technique a useful tool for the combinatorial analysis of phase transformations in thin films, especially when combined with the use of films with lateral composition gradients. As an illustration, we apply the technique to evaluate the thermomechanical behavior of Fe-Pd binary alloys as a function of composition. (C) 2008 American Institute of Physics.
Keywords: SHAPE-MEMORY ALLOYS; INTERNAL-STRESS; BEHAVIOR; COPPER; SILVER